Paradiplomasi sebagai Strategi Inovasi Pemerintahan Daerah: Penjajakan Kerja sama Lampung - Zagreb - Suharyadi, Irsyaad; Fitria, Arie; Fatharani, Fitri (Government Science Department , Faculty of Social and Political Science - University of Lampung. Journal of Government and Social Issues (JGSI), 2025)
This study analyzes the dynamics of paradiplomacy between Lampung Province and Zagreb City, Croatia. The findings indicate that the LampungZagreb relationship has met the determinant cause and favorable condition stages but has not yet reached the stage of paradiplomatic action that results in formal cooperation. Although the Lampung Provincial Government has demonstrated international engagement and political support, until now there has been no formal agreement, such as a Memorandum of Understanding (MoU) or Letter of Intent (LoI), with the Zagreb Government. The foundation of regional-level international relations between the two regions has only been built through ongoing academic collaboration. Since 2017, collaboration between the University of Lampung, Zagreb University, and Vern University, including joint summer schools, lecturer exchanges, joint research, and the Erasmus+ program, has established a consistent academic network and become a strategic entry point for initiating paradiplomacy. This study provides institutional strengthening of regional foreign cooperation and optimization of established academic networks so that Lampung-Zagreb paradiplomacy can develop into a model of regional government innovation with the potential to be replicated in other regions in Indonesia.